Recovery from chronic fatigue syndrome after treatments given in the PACE trial. - White, P; Goldsmith, K; Johnson, A; Chalder, T; Sharpe, M (2013)
BACKGROUND: A multi-centre, four-arm trial (the PACE trial) found that rehabilitative cognitive behaviour therapy (CBT) and graded exercise therapy (GET) were more effective treatments for chronic fatigue syndrome (CFS) than specialist medical care (SMC) alone, when each was added to SMC, and more effective than adaptive pacing therapy (APT) when added to SMC. In this study we compared how many participants recovered after each treatment. METHOD: We defined recovery operationally using multiple criteria, and compared the proportions of participants meeting each individual criterion along with two composite criteria, defined as (a) recovery in the context of the trial and (b) clinical recovery from the current episode of the illness, however defined, 52 weeks after randomization. We used logistic regression modelling to compare treatments. RESULTS: The percentages (number/total) meeting trial criteria for recovery were 22% (32/143) after CBT, 22% (32/143) after GET, 8% (12/149) after APT and 7% (11/150) after SMC. Similar proportions met criteria for clinical recovery. The odds ratio (OR) for trial recovery after CBT was 3.36 [95% confidence interval (CI) 1.64–6.88] and for GET 3.38 (95% CI 1.65–6.93), when compared to APT, and after CBT 3.69 (95% CI 1.77–7.69) and GET 3.71 (95% CI 1.78–7.74), when compared to SMC (p values < or =0.001 for all comparisons). There was no significant difference between APT and SMC. Similar proportions recovered in trial subgroups meeting different definitions of the illness. CONCLUSIONS: This study confirms that recovery from CFS is possible, and that CBT and GET are the therapies most likely to lead to recovery.